Framework for Environmental Protection in Nigeria - Adi, Odey Stephen (International Journal of Law and Society, 2023)
This article aims to examine the development of Nigeria's environmental legislation framework. Nigeria needs help balancing economic growth and natural resource preservation as a developing country. This duality is mirrored by severe ecological problems, such as the destruction of the marine environment in the Niger Delta by crude oil and groundwater contamination in Lagos, the country's largest megacity. This research method is in-depth on normative legal research methods/library research. This article argues that more progress has yet to be made despite the greater understanding of the need to protect natural resources. The massive and ongoing contamination of vital natural resources underscores this modest increase. Investigations revealed that the same administration that set up this facility was also one of the primary violators of environmental norms and regulations. This often results in a system failure atmosphere where nothing works, and the environment suffers. The possibility of employment, environmental protection and environmental sustainability are advantages of enforcing environmental standards. Among the barriers to effective compliance with environmental regulations are outdated laws; high cost of environmental standards; weak institutional capacity; bad government; staff shortage; inadequate funding; personal interests; overlapping or conflicting laws; ignorance; and lack of the rule of law.